Laser treatment of drug-induced gingival enlargement: overview of research of the last 50 years - Laurenta Lelia Mihai; Ioanina Parlatescu; Costina Lixandru; Paula Perlea (Romanian Journal of Stomatology, 2024)
Drug-induced gingival enlargement (overgrowth) occurs as a result of the use of systemic medication such as immunosuppressants, anticonvulsants, and calcium channel blockers. These medication classes treat important general conditions, which makes their use essential. Often, the hyperplasia that occurs as an adverse effect of the medication has a remarkable clinical aspect. An intricate, multidisciplinary approach is required, beginning with the replacement of causing medication and ending with the upkeep of strict hygiene. The need for research and the study of solutions that provide comfort to patients affected by the adverse effects of the administered medication is thus imposed. Our research summarizes the literature from the past 50 years on laser therapy for medication-induced gingival enlargement. The aim is to highlight the novel nature of using lasers as a treatment method as well as their beneficial therapeutic effects.